Olanzapine Promotes the Occurrence of Metabolic Disorders in Conditional TCF7L2-Knockout Mice - Yang, Ye; Shen, Manjun; Li, Li; Long, Yujun; Wang, Lu; Lang, Bing; Wu, Renrong (Frontiers in Cell and Developmental Biology, 2022)
Objectives: Schizophrenia (SCZ) patients display higher incidence of metabolic syndrome (MetS) and comorbidity of type II diabetes. Both atypical antipsychotics and genetic variants are believed to predispose the patients with the risk but their interplay remains largely unknown. TCF7L2 is one of the most common genes strongly associated with glucose homeostasis which also participates in the pathogenesis of schizophrenia. In this study, we aim to explore the regulatory roles of TCF7L2 in atypical antipsychotics-induced MetS. Methods: Mice with pancreatic β cell-specific Tcf7l2 deletion (CKO) were generated. The CKO mice and control littermates were subject to olanzapine (4 mg/kg/day) or saline gavage for 6 weeks. Metabolic indices, βcell mass and the expressing levels of TCF7L2 and GLP-1R in pancreatic tissue were closely monitored. Results: Tcf7l2 CKO mice displayed a spectrum of core features of MetS which included remarkably increased rate of weight gain, higher fasting insulin, higher values of blood lipids (cholesterol, triglyceride and low density lipoprotein), impaired glucose tolerance and hypertrophy of adipocytes. Notably, these effects could be further exacerbated by olanzapine. In addition, Tcf7l2 CKO mice with olanzapine group showed significantly decreased expression of GLP-1R protein and a trend of reduced pancreatic β-cell mass. RT-qPCR revealed that the CKO mice presented a significantly less transcription of Sp5, an important element of Wnt Signalling pathway. Conclusion: Our study illustrates that mice with pancreatic β cell-targeted Tcf7l2 deletion were more vulnerable to suffer metabolic abnormalities after olanzapine administration. This impairment may be mediated by the reduced expression of GLP-1R.